Development of a Promt Chatbot Application based on Rasa - Riansyah, Rafli; Rochman, Abdul; Budi Santoso, Gatot (Intelmatics, 2026)
Abstract: The development of artificial intelligence-based chatbots has increased the need for systems that can support interactive services efficiently. The Rasa framework is widely used in chatbot development due to its flexibility, but the prompt design process is still done manually by editing configuration files, making it difficult for non-technical users. This study aims to develop a web-based application that facilitates the design and management of Rasa-based chatbot prompts without the need for direct code editing. The system development method used is Waterfall, which includes the stages of requirements analysis, design, implementation, testing, deployment, and maintenance. The application was developed using the Laravel framework and integrated with the Rasa chatbot structure. System testing was conducted using the Black Box Testing method to ensure that the application functions as required. The results of the study show that the application simplifies the management of chatbot intents, training data, entities, and responses, thereby increasing efficiency and ease of use for users in designing Rasa-based chatbots.